Productivity and profitability of small-scale tilapia aquaculture in Myanmar - Tran, Nhuong; Hoong, Yan; Aung, Yee; Peart, Jeffrey; Akester, Michael J.; Khin, Maung Soe; Lwin, Aye Aye (WorldFish, 2022)
To promote the sustainable development of aquaculture in Myanmar, WorldFish and its partners implemented the Scaling Systems and Partnerships for Accelerated Adoption of Improved Tilapia Strains (SPAITS) project, funded by the German Federal Ministry for Economic Cooperation and Development and commissioned by the Deutsche Gesellschaft für Internationale Zusammenarbeit through the Fund International Agricultural Research. The goal was to increase the adoption of improved tilapia strains among poor fish producers and deliver improved productivity and profitability of small-scale aquaculture so that poor producers, particularly women, are able to exit poverty and natural resource systems are improved to sustain future fish production. The project’s purpose is to design systems that accelerate the dissemination and adoption of improved tilapia strains and aquaculture management practices developed by WorldFish, based on relevant gender-sensitive and contextual knowledge, that will enable poor small-scale fish farmers to have access to, adopt and benefit from improved strains of tilapia. As an activity of the project, this study focuses on assessing the performance of small-scale tilapia aquaculture operated by aquaculture households in Myanmar.